Leading indicators of German business cycles: An assessment of properties - Ulrich Fritsche; Sabine Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
A reliable leading indicator should possess the following properties: (1) The movements in the indicator series should resemble those in the business cycle reference series. (2) The relation between the reference series and the indicator should be statistically significant and stable over time. (3) The inclusion of the indicator in out-of-sample forecasting procedures should improve the predictive power. Our analysis deals with tests for these requirements applied to German data. We used frequency domain analysis, different Granger-causality tests and out-of sample forecasts. Only few indicators passed all tests. Their inclusion into VAR-based forecasts improves the forecast in the very short run. – – Brauchbare Frühindikatoren sollten folgende Eigenschaften besitzen: (1) Die konjunkturellen Bewegungen des Frühindikators sollten denen der Referenzreihe folgen. (2) Die Beziehung zwischen den Reihen sollte stabil und signifikant sein. (3) Die Einbeziehung des Indikators sollte die Out-of-sample-Prognose verbessern. Unsere Untersuchung testet diese Anforderungen für deutsche Daten. Dazu werden Methoden der Spektralanalyse, verschiedene Granger-Tests und Out-of-sample-Prognosen verwendet. Nur wenige Indikatoren bestehen die Tests auf die geforderten Eigenschaften. Ihre Einbeziehung in VAR-basierte Prognosen verbessert die Prognoseleistung in der sehr kurzen Frist.
Keywords: E32; L60; L70; 330; Konjunkturindikator; Konjunkturprognose; Prognoseverfahren; Statistischer Test; Schätzung; Deutschland